2020
DOI: 10.1155/2020/9497164
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Health Weight Loss Program in 250,000 Individuals

Abstract: Importance. Obesity is a worsening epidemic worldwide. Effective and accessible weight loss programs to combat obesity on a large scale are warranted, but a need for frequent face-to-face care might impose a limitation. Objective. To evaluate whether individuals following a weight loss program based on a mobile application, wireless scale, and nutritional program but no face-to-face care can achieve clinically significant weight loss in a large cohort. Design. Retrospective observational analysis. Setting. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…The increase in obesity rate and frequency are related to many causes like socioeconomic status, married life, and other lifestyle factors. [ 2 3 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…The increase in obesity rate and frequency are related to many causes like socioeconomic status, married life, and other lifestyle factors. [ 2 3 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…As frequent face-to-face care might impose a limitation for accessible programs, Senecal et al demonstrated that a weight loss program based on a mobile application, wireless scale, and nutritional program but no face-to-face care, can achieve clinically significant short-and midterm weight loss [10]. Weighing everyday matters.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that at 120 days after programme initiation, 62.7% of participants had lost at least 5% of their initial weight. 10 However, further investigations of the effects of this type of intervention on body composition, fat distribution and improvements in metabolic issues, such as abnormal blood pressure and insulin resistance, warrant further investigation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The MetaWell programme (Weijian Technologies, Hangzhou, China) is a commercial weight loss programme in China that integrates prepackaged food, online guidance and a wireless home scale and has been proven to be effective in a previous retrospective study. The results demonstrated that at 120 days after programme initiation, 62.7% of participants had lost at least 5% of their initial weight 10. However, further investigations of the effects of this type of intervention on body composition, fat distribution and improvements in metabolic issues, such as abnormal blood pressure and insulin resistance, warrant further investigation.…”
Section: Introductionmentioning
confidence: 96%